Effect of leakage current and dielectric constant on single and double layer oxides in MOS structure - Laha, Pinaki; Panda, A. B.; Dahiwale, S.; Date, Kalyani S.; Patil, K. R.; Barhai, P. K.; Das, A. K.; Banerjee, Indrani; Mahapatra, S. K. (Thin Solid Films, 2010)
MOS structure of Al/Al2O3/n-Si, Al/TiO2/n-Si and Al/Al2O3/TiO2/n-Si was obtained by deposition of Al2O3 and TiO2 on silicon substrate by RF Magnetron Sputtering system. The total thickness of the oxide layer similar to 40 +/- 5 nm in the MOS structure was kept constant. Samples were characterized by X-Ray diffraction (XRD). X-Ray photoelectron spectroscopy (XPS), Impedance analyzer and Current-voltage (J-V) characteristics. The variations in the dielectric constant and tan 8 of the MOS capacitor in the frequency range of 1000Hz-1MHz were measured by impedance analyzer. The variation in dielectric constant of the Al/Al2O3/TiO2/n-Si multilayer compared to single layer of Al/Al2O3/n-Si and Al/TiO2/n-Si is due to high probability of defects, lattice mismatch and interface interactions. The steep rise of Tan 6 values in the Al/Al2O3/TiO2/n-Si structure is due to the resonance effect of both Al2O3 and TiO2 layers. The leakage current mechanisms of MOS structures were extracted from Schottky coefficient and Poole-Frenkel coefficient. Theoretical values of Schottky coefficients (beta(SC)) and Poole-Frenkel coefficients (beta(PF)) for each sample were estimated using the real part of the dielectric constant. The experimental values were calculated from J-V characteristics and compared with theoretical values. The appropriate model has been proposed. It was found that Schottky and Poole-Frenkel mechanisms are applicable at low and high field respectively for all MOS structures. The combination of Al/Al2O3/TiO2/n-Si is found to be a promising structure with high dielectric constant and low leakage current suitable for MOS devices. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Al2O3; dielectric constant; Leakage current; MOS device; Poole-Frenkel emission; Schottky emission; TiO2